Thermal performance of Bangladesh traditional house during winter and summer seasons - Rashid, Rumana (2008)
Bangladesh traditional house is a typical example of dwelling which encapsulates the socio- cultural values of the country and traditional form. Currently, urban development in Bangladesh is threatening the traditional houses. Study on performance of traditional houses in Bangladesh is also rare compared to researches done on the contemporary or modern houses. Thus, the aim of this study is to evaluate the thermal performance of Bangladesh traditional houses in the context of Dhaka during summer and winter seasons. Quantitative method is used to measure the thermal performances. The field survey was conducted using thermal data loggers. A set of thermal data loggers were installed in selected Bangladesh traditional houses in Dhaka to record the air temperature of the indoor, outdoor and upper spaces. Data collection was carried out for duration of two months in winter and four months in summer. The research found that the traditional Bangladesh house is comfortable in both summer and winter seasons. It also noted that the thermal performance of traditional house depended on the different percentage of window openings in the upper space during both seasons. During the winter time as expected, closing the window openings throughout the day provided good thermal indoor environment. However, during summer seasons, closing the window openings of the upper space in the day time and opening them at night resulted in better thermal comfort indoor. This finding is important as it is contrary to the conventional belief of the occupants that opening their windows in the upper spaces during daytime in the summer will provide cooler indoor temperature. This study concludes that the use of upper spaces in Bangladesh traditional houses have significant impact on the overall indoor thermal performance. Thus, modern houses should consider employing this upper space to achieve thermal comfort.